The Global Drivers of Chronic Coastal Flood Hazards Under Sea‐Level Rise - Ben S. Hague; Shayne McGregor; David A. Jones; Ruth Reef; Doerte Jakob; Bradley F. Murphy (Earth's Future, 2023)
Abstract We present the first global estimates of annual average exceedances of contemporary minor, moderate, and major flood levels under sea‐level rise (SLR). Applying established methods, we show that minor flooding will occur most days worldwide under 0.7 m global SLR. Moderate flooding occurs at the same frequency under 1.0 m SLR. Local and regional differences in flood threshold elevations, tidal ranges, and non‐tidal variability lead to differences in the SLR required for this chronic flooding to emerge. Lower flood thresholds, smaller tidal ranges, and larger extreme skew surges mean chronic flooding can emerge with less SLR. We discuss several implications of these findings for coastal flood hazard assessments. First, tide‐driven water level variability dominates weather‐driven water level variability when determining locations' propensities for frequent and chronic flooding under SLR. Second, centimeter‐accurate flood threshold information is necessary to accurately estimate present and future flood hazards. Third, locations with the most frequent floods at present may not be those that have the most frequent floods under SLR. We develop the Rapid Assessment Framework for Frequent Flood Transitions under SLR (RAFFFTS) to apply these findings to locations not previously considered in global coastal flood hazard studies. RAFFFTS can robustly identify potential future tidal flooding hotspots using only 1‐year observational records. We anticipate RAFFFTS will be a valuable tool for identifying locations at risk of chronic flooding under SLR, complementing existing tools for identifying changes in less frequent episodic floods.